2010
DOI: 10.1186/1756-0500-3-186
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological profile of sinonasal masses: an experience in national ear care center Kaduna, Nigeria

Abstract: BackgroundThe presence of a mass in the nose and paranasal sinuses may seem to be a simple problem; however it raises many questions about the differential diagnosis. The aim of this study is to evaluate the clinico-pathological profile of sinonasal masses in our environmentThis is a retrospective analytical review of all the patients with sinonasal masses that presented to the national ear care center, Kaduna over a six year (2003-2008) period. Their biodata, clinical profile and histological diagnoses were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
67
7
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 12 publications
34
67
7
1
Order By: Relevance
“…Nasal polyps had slight predilection for males in our study, (male:female ratio of 1.3:1). It was similar to various studies [27,28] but a study from Nigeria showed female preponderance (M:F = 1:1.2) [30]. There was a marked gender difference in controls (M:F = 10.6:1).…”
Section: Resultssupporting
confidence: 91%
“…Nasal polyps had slight predilection for males in our study, (male:female ratio of 1.3:1). It was similar to various studies [27,28] but a study from Nigeria showed female preponderance (M:F = 1:1.2) [30]. There was a marked gender difference in controls (M:F = 10.6:1).…”
Section: Resultssupporting
confidence: 91%
“…Bakari et al in 2010 had reported a peak incidence of 33years. 7 This seems to be accordance with our study.…”
Section: Resultssupporting
confidence: 83%
“…Bakari et al, reported a peak incidence of 33 years. 20 Larsen et al, reported similar results of 252 danish patients. They observed nasal polyposis most commonly in patients who were 40-60 years old.…”
Section: Age and Sex Distributionsupporting
confidence: 71%